Metal Complexes with Substituted Biphenyls - Ranjan Jha, Raj; Mishra, J.P.; Jha, D.K. (Asian Journal of Chemistry, 2010)
Metal complexes of the type [MLX2] where M = Co(II) Ni(II) and Cu(II), L = 3,3´-dimethyl-4,4´-bis(benzoylthiourea) biphenyl or 3,3´-dimethyl-4,4´-bis-(thiocarbamoyl) biphenyl and X = Cl–, Br–, NO–3 and ClO–4 have been isolated from the neutral medium. octahedral geometry for the complexes has been proposed on the basis of elemental analysis, magnetic moment and spectral studies. The coordination of the metal ions to the ligand through sulphur and carbamoyl oxygen atom in the case of formal ligand whereas through sulphur and carbamoyl nitrogen atom to the later ligand has been proposed basing on IR spectra. Fungicidal screening of the complexes shows them to be active against Aspergillus niger, Fusarium oxysporium and Helminthmporium oryzae.